Why Huddle? Ecological Drivers of Chick Aggregations in Gentoo Penguins, Pygoscelis papua, across Latitudes. - Caitlin Black; Ben Collen; Daniel Johnston; Tom Hart (PLoS ONE, 2016)
Aggregations of young animals are common in a range of endothermic and ectothermic species, yet the adaptive behavior may depend on social circumstance and local conditions. In penguins, many species form aggregations (aka. crèches) for a variety of purposes, whilst others have never been observed exhibiting this behavior. Those that do form aggregations do so for three known benefits: 1) reduced thermoregulatory requirements, 2) avoidance of unrelated-adult aggression, and 3) lower predation risk. In gentoo penguins, Pygoscelis papua, chick aggregations are known to form during the post-guard period, yet the cause of these aggregations is poorly understood. Here, for the first time, we study aggregation behavior in gentoo penguins, examining four study sites along a latitudinal gradient using time-lapse cameras to examine the adaptive benefit of aggregations to chicks. Our results support the idea that aggregations of gentoo chicks decrease an individual's energetic expenditure when wet, cold conditions are present. However, we found significant differences in aggregation behavior between the lowest latitude site, Maiviken, South Georgia, and two of the higher latitude sites on the Antarctic Peninsula, suggesting this behavior may be colony specific. We provide strong evidence that more chicks aggregate and a larger number of aggregations occur on South Georgia, while the opposite occurs at Petermann Island in Antarctica. Future studies should evaluate multiple seabird colonies within one species before generalizing behaviors based on one location, and past studies may need to be re-evaluated to determine whether chick aggregation and other behaviors are in fact exhibited species-wide.